TRANSFORMING TEACHER CAPACITY THROUGH PROFESSIONAL DEVELOPMENT, MOTIVATION, AND ORGANIZATIONAL SUPPORT - Maria Ulfah; Achmadi Achmadi; Munawar Thoharudin (Nurul Jadid University, Paiton Probolinggo, East Java, 2025)
This study examines teacher capacity transformation through professional development, work motivation, and organizational support in the context of 21st-century education. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among variables. Data were collected from economics teachers at senior high schools and vocational schools in Pontianak City who are members of the Subject Teacher Forum (MGMP). The results reveal that professional development exerts the strongest influence on teacher capacity transformation, followed by organizational support and work motivation. Work motivation partially mediates the relationship between organizational support and teacher capacity transformation but does not mediate the effect of professional development on teacher capacity transformation. These findings indicate that professional development is the primary driver of teacher capacity enhancement, while organizational support contributes both directly and indirectly through increased motivation. The study offers an integrated Human Resource Management (HRM)-based model and provides practical implications for educational policymakers in strengthening teacher development strategies.